Effect of BIS-guided anesthesia on emergence delirium following general anesthesia in children: A prospective randomized controlled trial - Frelich, Michal; Lečbychová, Karolína; Vodička, Vojtěch; Ekrtová, Tereza; Sklienka, Peter; Jor, Ondřej; Straková, Hana; Bílená, Markéta; Formánek, Martin; Burša, Filip (Anaesthesia, critical care & pain medicine, 2024)
OBJECTIVE: Emergence delirium (ED) is a postoperative complication in pediatric anesthesia characterized by a perception and psychomotor disorder, with a negative impact on postoperative recovery. As the use of inhalation anesthesia is associated with a higher incidence of ED, we investigated whether titrating the depth of general anesthesia with BIS monitor can reduce the incidence of ED. DESIGN: Randomized, prospective, and double-blind. SETTING: Patients undergoing endoscopic adenoidectomy under general anesthesia according to a uniform protocol. PATIENTS: A total of 163 patients of both sexes aged 3-8 years were enrolled over 18 months. INTERVENTIONS: Immediately after the induction of general anesthesia, a bispectral index (BIS) electrode was placed on the patient's forehead. In the study group, the depth of general anesthesia was monitored with the aim of achieving BIS values of 40-60. In the control group, the dose of sevoflurane was determined by the anaesthesiologist based on MAC (minimum alveolar concentration) and the end-tidal concentration. MEASUREMENTS: The primary objective was to compare the occurrence of ED during the PACU (post-anesthesia care unit) stay in both arms of the study. The secondary objective was to determine the PAED score at 10 and 30 min in the PACU and the need for rescue treatment of ED. MAIN RESULTS: 86 children were randomized in the intervention group and 77 children in the control group. During the entire PACU stay, 23.3% (38/163) of patients developed ED with PAED score >10: 35.1% (27/77) in the control group and 12.8% (11/86) in the intervention group (p = 0.001). Lower PAED scores were also found in the intervention group at 10 (p < 0.001) and 30 (p < 0.001) minutes compared to the control group. The need for rescue treatment did not differ between groups (p = 0.067). CONCLUSION: Individualization of the depth of general anesthesia with BIS monitoring is an effective method of preventing ED in children. CLINICAL TRIAL REGISTRATION: NCT04466579.
Keywords: Female; dítě; předškolní dítě; ženské pohlaví; pooperační delirium; sevofluran; Anesthesia, General; lidé; celková anestezie; inhalační anestezie; Sevoflurane; prospektivní studie; Male; Prospective Studies; Emergence Delirium; Child, Preschool; Anesthesia, Inhalation; Child; mužské pohlaví; probouzení z anestezie; Anesthesia Recovery Period; Humans